Fabrication of Thylakoid Membrane-Based Photo-Bioelectrochemical Bioanode for Self-Powered Light-Driven Electronics - Amit Sarode; Gymama Slaughter (Energies)
The transition toward sustainable and decentralized energy solutions necessitates the development of innovative bioelectronic systems capable of harvesting and converting renewable energy. Here, we present a novel photo-bioelectrochemical fuel cell architecture based on a biohybrid anode integrating laser-induced graphene (LIG), poly(3,4-ethylenedioxythiophene) (PEDOT), and isolated thylakoid membranes. LIG provided a porous, conductive scaffold, while PEDOT enhanced electrode compatibility, electrical conductivity, and operational stability. Compared to MXene-based systems that involve complex, multi-step synthesis, PEDOT offers a cost-effective and scalable alternative for bioelectrode fabrication. Thylakoid membranes were immobilized onto the PEDOT-modified LIG surface to enable light-driven electron generation. Electrochemical characterization revealed enhanced redox activity following PEDOT modification and stable photocurrent generation under light illumination, achieving a photocurrent density of approximately 18 µA cm−2. The assembled photo-bioelectrochemical fuel cell employing a gas diffusion platinum cathode demonstrated an open-circuit voltage of 0.57 V and a peak power density of 36 µW cm−2 in 0.1 M citrate buffer (pH 5.5) under light conditions. Furthermore, the integration of a charge pump circuit successfully boosted the harvested voltage to drive a low-power light-emitting diode, showcasing the practical viability of the system. This work highlights the potential of combining biological photosystems with conductive nanomaterials for the development of self-powered, light-driven bioelectronic devices.